Timang Cenggok Song in Tanjungbalai City : Character Value Analysis and Music Composition - Ningsih, Maya; Triyanto, Triyanto; Sumaryanto Florentinus, Totok (Universitas Negeri Semarang, 2019)
Timang Cenggok song is a traditional song that is developed in Tanjungbalai City society, this song is usually sung when the mother is going to put the child to sleep. The lyrics in Timang Cenggok song that is sung by a mother for her child aims to give character education. This study aims to examine the character values ​​contained in the Timang Cenggok song and the musical aspects of the Timang Cenggok song. The location of the research is Tanjungbalai City, North Sumatra Province. Data collection techniques are observation, interview, and document study. The data validity technique uses source triangulation. The data analysis technique uses descriptive analysis. The results of this study are the Timang Cenggok song contains the character value that aims to build the child's personality into a religious person, has a good moral and be able to socialize in the community. Timang Cenggok song has musical aspects in the form of melodies with varying intervals, different rhythm patterns between one bar and the other bar, and the harmony that can be written based on chords using music theory. This research can broaden the perspective of the reader about Timang Cenggok song and provide information about the description of Timang Cenggok song which contains the character values and knowledge of the music composition of Timang Cenggok song.